FEASIBILITY REPORT ON INTRODUCTION OF THE INTELLECTUAL CONTROL SYSTEM FOR IRON ORE BENEFICATION PROCESS - Kupin, А. І. (Radio Electronics, Computer Science, Control, 2010)
The block diagram of the prototype of an iron ore magnetic separation intellectual control system is presented. On the basis of industrial tests results cost-effectiveness of this system introduction at the concentration plant has been estimated.